2016
DOI: 10.9778/cmajo.20150116
|View full text |Cite
|
Sign up to set email alerts
|

Wait times to rheumatology care for patients with rheumatic diseases: a data linkage study of primary care electronic medical records and administrative data

Abstract: Background:The Wait Time Alliance recently established wait time benchmarks for rheumatology consultations in Canada. Our aim was to quantify wait times to primary and rheumatology care for patients with rheumatic diseases. Methods:We identified patients from primary care practices in the Electronic Medical Record Administrative data Linked Database who had referrals to Ontario rheumatologists over the period 2000-2013. To assess the full care pathway, we identified dates of symptom onset, presentation in pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
49
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 38 publications
0
49
2
1
Order By: Relevance
“…This trend may be a reflection of rheumatologists declining these types of referrals in more recent years and instead seeing more patients with systemic inflammatory conditions, and/or fewer referrals to rheumatologists for these noninflammatory conditions. Indeed, in a study of 2430 patients referred to a rheumatologist in Ontario, 17% did not result in a rheumatology consultation 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This trend may be a reflection of rheumatologists declining these types of referrals in more recent years and instead seeing more patients with systemic inflammatory conditions, and/or fewer referrals to rheumatologists for these noninflammatory conditions. Indeed, in a study of 2430 patients referred to a rheumatologist in Ontario, 17% did not result in a rheumatology consultation 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, changes to rheumatology wait times over time are unknown; however, wait times exceed established benchmarks 10 . An alternative explanation to the reduction in new consultations is that some patients (such as those with regional MSK conditions) are being referred to other care providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While benchmarks for time to referral to rheumatologic consultation are unmet, the Widdifield, et al study suggests that this is not the most significant bottleneck from symptom onset to management 6 . The study further dissects the median 327 days from RA symptom onset to rheumatologist consultation, revealing that the majority of the time was spent preconsultation (median 173 days from symptom onset to primary care visit, and median 115 days from first mention at primary care to rheumatology referral).…”
Section: Rheumatologymentioning
confidence: 99%
“…A contemporary and enlightening study by Widdifield and colleagues found an equal proportion of referrals made for osteoarthritis (OA) and systemic inflammatory rheumatic diseases, with each accounting for about one-third of the consultations requested 6 . Herein lies an opportunity, as many rheumatologists believe OA care falls predominantly within the realm of primary care.…”
Section: Rheumatologymentioning
confidence: 99%